The Views of Science and Art Center (SAC) Students Regarding Socratic Inquiry Seminars - Asiye BAHTİYAR; Bilge CAN (Anı Publishing, 2021)
The purpose of this study is to determine the views of students attending Science and Art Centers (SAC) about Socratic research seminars. This qualitative study was conducted with nine undergraduate students. Individual interviews were conducted with students after the seminars, which spanned 10 weeks, about their opinions of the seminars. As a result of the content analysis, it was found that students rated the Socratic research process as a process in which they can freely express their thoughts, have a scientific experience that contributes to their development, individual differences come out, a good method is used for the development of the discussion, questions and discussions about science are held. In addition, students believe that at the end of the seminars, they can ask better questions both quantitatively and qualitatively, change their ideas, question themselves, develop their sense of curiosity, emphatically respond to different opinions and make philosophical inquiries.